QTL mapping of selenium content using a RIL population in wheat. - Pei Wang; Huinan Wang; Qing Liu; Xia Tian; Yanxi Shi; Xiaocun Zhang (PLoS ONE)
Selenium (Se) is an essential trace element that plays various roles in human health. Understanding the genetic control of Se content and quantitative trait loci (QTL) mapping provide a basis for Se biofortification of wheat to enhance grain Se content. In the present study, a set of recombinant inbred lines (RILs) derived from two Chinese winter wheat varieties (Tainong18 and Linmai6) was used to detect QTLs for Se content in hydroponic and field trials. In total, 16 QTLs for six Se content-related traits were detected on eight chromosomes, 1B, 2B, 4B, 5A, 5B, 5D, 6A, and 7D. Of these, seven QTLs were detected at the seedling stage and nine at the adult stage. The contribution of each QTL to Se content ranged from 7.37% to 20.22%. QSsece-7D.2, located between marker loci D-3033829 and D-1668160, had the highest contribution (20.22%). This study helps in understanding the genetic basis for Se contents and will provide a basis for gene mapping of Se content in wheat.